Management pathway for emergency department patients in the setting of the opioid epidemic and emergency department overcrowding - Gurley, Kiersten (Clin Exp Emerg Med, 2020)
OBJECTIVE: The United States is currently in the midst of a major opioid addiction epidemic, of which the primary drivers are a sharp increase in prescription opioid pain medications, their misuse, and the inordinate illicit use of opioids. Declared a national health emergency, the opioid crisis puts enormous pressure on various systems, including increasing overcrowding in emergency departments (EDs) and forced changes in prescribing practices. We are piloting a newly-developed ED opiate pathway to streamline ED care for patients who frequently present at the ED for chronic pain management or other recurrent pain-causing medical problems. METHODS: Patients at risk of possible opioid addiction are identified and their records are reviewed. If there is no narcotics agreement in place, the ED care team contacts the primary care physician and any other service providers involved in the patient’s care to create a comprehensive pain management program. RESULTS: Our pathway is simple and geared toward streamlining and improving care for patients with opioid addiction and misuse. We looked at seven patients in this pilot study with mixed results regarding decreasing future ED visits. CONCLUSION: This strategy may both limit opioid usage and abuse as well as limit ED visits and overcrowding by streamlining ED care for patients who frequently present for chronic pain management or other recurrent medical problems.